Qualidade de vida dos acadêmicos de enfermagem da Universidade Federal do Pará - SOUZA, Joyce Gama (2020)
Although there is no consensus regarding the concept of quality of life, the World Health Organization defines as the individual's perception about your position in life, in the context of their culture and system of values in which they live and in relation to their expectations, standards and concerns. In this sense, it is essential to the study of the quality of life of nursing students, since the theme is associated with the increasing number of chronic diseases and psychological that can deteriorate during the academic day. The objective of this study is to analyze the quality of life of the academics of nursing course at Federal University of Pará. It is a descriptive quantitative study with the use of the statistical technique exploratory data analysis. The results are based on escores represented by Likert psychometric model, which has a numerical scale from 1 to 5 points where the level of intensity, capacity, frequency or satisfaction follows the growing scale modeling. It has been noted that in relation to the overall quality of life, 36 (22.01%) students evaluate their quality of life while scholar as bad or very bad. In relation to the assessment of health most claims to be dissatisfied (38.99%). In the physical domain, the highest escore of quality of life was observed in facet of energy and fatigue (3.34) and the worst escores in the facets of sleep and rest (2.85), dependence on medication and treatment (2.77) and daily activities (2.35). In the psychological domain, the highest escore was observed in the facet of spirituality, religion and personal beliefs (3.57%) and the worst escores were assigned to the facets of self-esteem (2.95), negative feelings (2.84) and positive feelings (2.81). All facets of the social relationships domain received approximate escores, namely, social support (support) (3.47), personal relations (3.34) and sexual activity (3.23). In the field environment the best escore was attributed to the environment at home (3.29) and the worst to physical security and protection (2.74), physical environment (2.63), financial resources (2.40), transportation (2.16) and participation and opportunities for recreation and leisure in the university campus (2.00). The area that received the maximum escore was the social relations (3.35) and the worst escore was attributed to the environment domain. In relation to the association between the escores and sociodemographic characteristics, it is perceived that the best escore was attributed to the social relations (4.06) by academics with family income of seven or more minimum wage and the worst escore was also assigned to the same domain by scholar declared yellow (1.33). In addition, realize low escores related to the physical domain in the categories of gender, skin color/ethnicity, marital status and family income. There are still a few escores low in areas of psychological and social relations, and very poor escores in the environment domain in all categories.